Implementation of the K-Means Algorithm on Learning Outcomes and Self-Regulated Learning - Anisatul Farida; Nugroho Arif Sudibyo (UNION : Jurnal Ilmiah Pendidikan Matematika, 2022)
This study aims to apply data mining to Student Self-Regulated Learning and learning outcomes in online learning in higher education using the k-means algorithm. The cluster analysis method in this research is the k-means method. The research was conducted by taking data from students who took the Statistical course Informatics Engineering, the faculty of Computer Science at Duta Bangsa University Surakarta. The number of student data was 22 data. The results show that the number of clusters according to the k-means algorithm is 3.